(untitled) (International journal of artificial intelligence, 2025)
This article explores the use of metaphors and symbols in the English and Uzbek languages from a comparative linguistic and cultural perspective. It analyzes how metaphorical expressions and symbolic imagery reflect the unique worldview, historical background, and national identity of each linguistic community. By examining selected examples from literature, proverbs, and everyday speech, the study identifies both universal and culturally specific features of metaphor and symbol usage. The article highlights the cognitive and communicative functions of these linguistic devices and discusses their role in shaping conceptual frameworks. The research findings contribute to a deeper understanding of cross-cultural semantics and support effective intercultural communication and translation practices.